2020
DOI: 10.1016/j.lfs.2020.118114
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of IL-6 and NLRP3 inflammasome as potential therapeutic targets to combat COVID-19: Role of lncRNAs in cytokine storm modulation

Abstract: The world has witnessed a high morbidity and mortality caused by SARS-CoV-2, and global death toll is still rising. Exaggerated inflammatory responses are thought to be more responsible for infiltrated immune cells accumulation, organ damage especially lung, dyspnea, and respiratory failure rather than direct effect of viral replication. IL-6 and NLRP3 inflammasome are the major immune components in immune responses stimulation upon pathogen infection. It's noteworthy that the function and expression of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 145 publications
2
71
0
Order By: Relevance
“…IL-6 is known for downstream target of IL-1β, consequently activated and increased in patients with NLRP3 inflammasome related diseases 9 . Recently, it has been reported that IL-6 and NLRP3 inflammasome are main regulator in immune response stimulated by pathogen and viral infection such as SARS-CoV-2 10 . Additionally, TNF-α also has a function on the activation of NLRP3 inflammasome components in inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…IL-6 is known for downstream target of IL-1β, consequently activated and increased in patients with NLRP3 inflammasome related diseases 9 . Recently, it has been reported that IL-6 and NLRP3 inflammasome are main regulator in immune response stimulated by pathogen and viral infection such as SARS-CoV-2 10 . Additionally, TNF-α also has a function on the activation of NLRP3 inflammasome components in inflammatory diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Paniri et al. [ 54 ] proposed that glyburide might be a useful drug to combat SARS-CoV-2 by blocking the wide spectrum of molecules related to inflammatory cascade. Certainly, these in silico predictions will require the in vitro target validation experiments in the future.…”
Section: Resultsmentioning
confidence: 99%
“…The NLRP3 inflammasome is a critical cytosolic protein complex responsible for both acute and chronic inflammation in response to various pathogens 27 , including SARS-CoV-2. 28 , 29 Anti-inflammatory diets are associated with improved pulmonary function in non-asthmatic Hispanic adults 30 and improved lung function and lower mortality in individuals with COPD. 31 Anti-inflammatory diets emphasize the inclusion of herbs and spices which have known antioxidant and anti-inflammatory effects and may slow the progression of COPD in which NLRP3 inflammasome activation plays a critical pathogenic role.…”
Section: Dietmentioning
confidence: 99%